2000
DOI: 10.1021/ol005791o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Enantiopure Termini-Differentiated Heptane Stereotriads.1 Application to Side Chain-Functionalized Tetrahydrofurans of IKD-8344

Abstract: Enantiopure epoxy cycloheptenyl sulfones syn-7b and anti-7b are prepared in five high-yielding and stereospecific operations from 1, 3-cycloheptadiene. These substrates serve as effective precursors for cis- and trans-substituted tetrahydrofurans (12, 10) which are segments of the antineoplastic agent IKD-8344.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Recently, the regioselective intramolecular alkylation observed in cycloheptadienyl epoxyvinyl sulfones was explained in terms of a bidentate coordination of the acid catalyst with both the epoxide and the sulfonyl oxygen atoms. [19] Our results indicate that there is an intrinsic preference, albeit modest, for a bicyclic 6/5 ring system over the other (path b vs. path a, Figure 4), without the intervention of any chelated activating functionality.…”
Section: Copper-catalysed Additions Of Grignard Reagents To Vinyl Diementioning
confidence: 63%
“…Recently, the regioselective intramolecular alkylation observed in cycloheptadienyl epoxyvinyl sulfones was explained in terms of a bidentate coordination of the acid catalyst with both the epoxide and the sulfonyl oxygen atoms. [19] Our results indicate that there is an intrinsic preference, albeit modest, for a bicyclic 6/5 ring system over the other (path b vs. path a, Figure 4), without the intervention of any chelated activating functionality.…”
Section: Copper-catalysed Additions Of Grignard Reagents To Vinyl Diementioning
confidence: 63%
“…It was found that the catalyst can be lowered to 1 mol% without significant loss of yield or ee, but the reaction time was overly long. This problem was overcome by using 100 mol% of NH 4 OAc; other possible co-catalysts were screened at various temperatures but none were as efficient as NH 4 OAc. This modification combined with the 1 mol% catalyst loading, made it possible to run the reaction in a reasonable time period with excellent results, but active catalyst can no longer be recovered (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…The solid product was washed with water (2 L) and dried by forcing air through the filter cake for 24 h to give a pure and pale yellow solid (2, 1.1 kg, 51% yield over 5 steps from cyclohexanone, 98% purity by HPLC); mp 58-60 °C (lit. 2 4 OAc is dissolved before proceeding further. The Jacobsen Mn catalyst (8.3 g, 0.01 mol) was then added and the solution immediately turned brown (due to the catalyst).…”
Section: -(Phenylsulfonyl)-13-cyclohexadiene (2); Typical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…5-Hydroxypentenes have received much attention as synthetic intermediates for synthesis of biologically active tetrahydrofuran derivatives. [1][2][3][4][5][6][7][8][9][10][11] 5-Hydroxypentenes have been prepared by the reactions of allylic organometallics of indium, 12 magnesium, 13 and tin, 13 with epoxide or cyclopropylmethylmagnesium bromide 14 with aldehyde. A mixture of regioisomeric alcohols was generally produced.…”
Section: Introductionmentioning
confidence: 99%